Pengaruh Inflasi, Kurs, BI Rate, dan Harga Emas Dunia Terhadap Jakarta Islamic Index (JII) Periode 2020-2022 - Sjam, Dewi; Chrisananda, Riska Anin; Rusgianto, Sulistya (Universitas Negeri Surabaya, 2023)
As a country with tremendous potential due to its large Muslim population, the Islamic capital market receives the most attention. This country's sharia-based capital market has grown more competitive since the Jakarta Islamic Index (JII) was issued as an index of stock prices. Various macroeconomic variables, spanning from external to internal factors, have been studied in relation to JII equities. This study will investigate the simultaneous and partial effects of external factors on JII stock prices, including inflation, exchange rates, interest rates, and the price of gold on a global scale. This is a form of quantitative research that utilizes secondary data sources. The research population consists of monthly data from the dependent and independent variables. Only the interest rate (BI Rate) was found to have no significant effect on JII stock prices. While other variables have a significant and positive impact. The Jakarta Islamic Index (JII) stock price is influenced by the inflation rate, the exchange rate, and the price of gold on a global scale. Although partially, neither the interest rate nor the BI rate affects Islamic stock prices. Nonetheless, 67% of the macroeconomic variables have a significant influence on the JII stock price simultaneously, while the remaining 33% are influenced by other variables.